2012
DOI: 10.3109/0886022x.2011.647305
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Montelukast against Cisplatin-Induced Acute Renal Damage in Rats

Abstract: Objective: In this study, the therapeutic and protective effects of montelukast against cisplatin (CP)-induced acute renal damage were investigated. Materials and Methods: Thirty-five female rats were divided into five groups as follows: (1) control, (2) montelukast (10 mg/kg daily for 10 days per-oral (p.o.), (3) CP (single dose 7 mg/kg intraperitoneally (i.p.)), (4) CP + montelukast (10 mg/kg daily for 10 days p.o., after 3 days of the injection of CP), (5) montelukast (10 mg/kg daily for 10 days p.o.) + CP … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 46 publications
3
9
0
Order By: Relevance
“…The currently reported ML renoprotective efficacy against CIS is supported by a another study by Beytur et al . Since both LTR blocking and 5‐lipoxygenase inhibition confer renoprotection in CIS injury, hence LT plays a crucial role in such an ailment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The currently reported ML renoprotective efficacy against CIS is supported by a another study by Beytur et al . Since both LTR blocking and 5‐lipoxygenase inhibition confer renoprotection in CIS injury, hence LT plays a crucial role in such an ailment.…”
Section: Discussionmentioning
confidence: 99%
“…In renal dysfunction and urinary bladder sensitivity, ML protective potential is linked to the inhibition of release of inflammatory and oxidative stress mediators . ML protects against methotrexate and cisplatin (CIS) nephrotoxic effects. The latter authors showed that ML renoprotection is a function of the reduced oxidative stress and neutrophil infiltration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are experimental data suggesting that nephrotoxic drugs may also change the levels of BUN and SCr [22,23,24], which are commonly used to monitor the development and extent of renal tubular damage due to DDP [25]. Therefore, in this study we examined the levels of BUN and SCr after the application of DDP.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that CIS causes nephrotoxicity and nephrotoxicity is a strong factor to restrict usage of CIS 18 . In the present study; the deterioration of kidney functions was shown by increased serum BUN level, histopathological images of kidney as tubular epithelial necrosis, luminal necrotic debris and tubular dilatation and also histopathological kidney score in CIS administrated group.…”
Section: Discussionmentioning
confidence: 99%